Graphene oxide – molybdenum disulfide hybrid membranes for hydrogen separation - Ostwal, Mayur; Shinde, Digambar B.; Wang, Xinbo; Gadwal, Ikhlas; Lai, Zhiping (Journal of membrane science, 2018)
Graphene oxide – molybdenum disulfide hybrid membranes were prepared using vacuum filtration technique. The thickness and the MoS2 content in the membranes were varied and their H2 permeance and H2/CO2 selectivity are reported. A 60nm hybrid membrane containing ~ 75% by weight of MoS2 exhibited the highest H2 permeance of 804 × 10−9mol/m2sPa with corresponding H2/CO2 selectivity of 26.7; while a 150nm hybrid membrane with ~ 29% MoS2 showed the highest H2/CO2 selectivity of 44.2 with corresponding H2 permeance of 287 × 10−9mol/m2sPa. The hybrid membranes exhibited much higher H2 permeance compared to graphene oxide membranes and higher selectivity compared to MoS2 membranes, which fully demonstrated the synergistic effect of both nanomaterials. The membranes also displayed excellent operational long-term stability. •GO-MoS2 hybrid membranes exhibited high selectivity and high permeance.•GO assists in packing the MoS2 nanosheets.•The membranes were stable under long term testing.